The use of blended learning model based on quizizz application in improving english learning outcomes - Lanlan Muhria; Wily Wandari (Universitas PGRI Madiun, 2022)
Technology is advancing quickly, and one example of this is the spread of computer networks and internet services into practically every sphere of daily life. As long as they are connected to a computer network system via the internet, educators and students can engage and communicate anytime, anywhere, without being constrained by place or time, thanks to technology. This study uses a descriptive qualitative action research methodology in the classroom. This study is a staged, multi-cycle controlled investigative method designed to identify and address learning issues in the classroom. The 32 of AKPER YPIB Majalengka students who participated in this study were the subjects. The deployment of blended learning based on the Quizizz application can increase student learning outcomes, notably in the cognitive element, where students in cycle II have acquired a learning mastery of 96.88%, which can be inferred from the description and analysis of the research. Based on the study's findings, it can be concluded that Quizizz application-based blended learning can enhance student learning outcomes in English classes. The improvement is evident in the rise in student test scores since each learning cycle was put into place.